BILAMINARNI DERMALNI ZAMENIK INTEGRA U REKONSTRUKCIJI DEFEKTA POGLAVINE SA EKSPONIRANOM DUROM KOD PACIJENTA ZRAČENOG ZBOG TINEE CAPITIS U DETINJSTVU – PRIKAZ SLUČAJA - Stojičić, Milan; Jurišić, Milana; Nikolić Živanović, Maja; Jovanović, Milan; Stojanović, Marina; Jović, Marko; Jeremić, Jelena; Marinković, Milana (Medical Research, 2024)
Introduction: Before the discovery of antimycotics powerful enough to penetrate the hair follicle, the use of X ray radiation was a worldwide accepted method for scalp epilation as part of the treatment for tinea capitis in children. More than five decades later, the consequences of radiation in ringworm therapy have become evident and included high rates of recurrent and aggressive forms of non-melanoma skin tumors, brain tumors and meningiomas, as well as osteoradionecrosis. Scalp reconstruction presents a challenge due to the unique anatomic characteristics of the scalp as well as tissue inelasticity. Cases of bilaminar dermal regeneration templates applied directly on dura in the literature are seldom described.Case report: A male patient irradiated due to tinea capitis as a child, presented at our Institution for management of multiple recurrent infiltrative basocellular carcinomas (BCC) and osteoradionecrosis of the scalp. Severe skin atrophy affected all areas of the scalp except for the forehead, which showed moderate atrophy. The patient had multiple surgeries over the next few years due to the emergence of new and recurrent BCCs as well as zones of osteoradionecrosis of the scalp. Post-surgical defects were commonly reconstructed using local fasciocutaneous flaps and skin autografts. Surgical site complications, including partial flap necrosis or autograft loss, frequently followed the procedures. After exhausting all reconstructive options by repeated previous surgeries, a post-surgical defect following ostectomy of newly developed ORN in the occipital region was reconstructed using a dermal substitute applied directly on the dura and covered with a skin autograft, in a two-step procedure. Due to a high perioperative risk for general anesthesia, the intervention was performed under local anesthesia with anesthesiologic monitoring. The postoperative period was uneventful and the skin autograft had a 100% take.Conclusion: The use of bilaminar dermal regeneration template Integra® can be efficiently utilized for reconstruction of full thickness skin and calvaria defects in complex cases when all other reconstructive methods are exhausted.